Modified value stream mapping of airport check-in procedures - O’Connor, Brian Edward (2014)
In June 2014 Brazil hosted the FIFA World Cup and in August 2016 Rio de Janeiro hosts the Summer Olympics. These two seminal sporting events will draw tens of thousands of air travelers through Brazil’s airports, airports that are currently in the midst of a national modernization program to address years of infrastructure neglect and insufficient capacity. Raising Brazil’s major airports up to the standards air travelers experience at major airports elsewhere in the world is more than just a case of building or remodeling facilities, processes must also be examined and reworked to enhance traveler experience and satisfaction. This research paper examines the key interface between airports and airline passengers—airport check-in procedures—according to how much value and waste there is associated with them. In particular, the paper makes use of a value stream mapping construct for services proposed by Martins, Cantanhede, and Jardim (2010). The uniqueness of this construct is that it attributes each activity with a certain percentage and magnitude of value or waste which can then be ordered and prioritized for improvement. Working against a fairly commonly expressed notion in Brazil that Brazil’s airports are inferior to the airports of economically advanced countries, the paper examines Rio’s two major airports, Galeão International and Santos Dumont in comparison to Washington D.C.’s Washington National and Dulles International airports. The paper seeks to accomplish three goals: - Determine whether there are differences in airport passenger check-in procedures between U.S. and Brazilian airports in terms of passenger value - Present options for Brazilian government or private sector authorities to consider adopting or implementing at Brazilian airports to maximize passenger value - Validate the Martins et al. construct for use in evaluating the airport check-in procedures Observations and analysis proved surprising in that all airports and service providers follow essentially the same check-in processes but execute them differently yet still result in similar overall performance in terms of value and waste. Although only a few activities are categorized as completely wasteful (and therefore removed in the revised value stream map of check-in activities), the weighting and categorization of individual activities according to their value (or waste) presents decision-makers a means to prioritize possible corrective actions. Various overall recommendations are presented based on this analysis. Most importantly, this paper demonstrates the viability of using the construct developed by Martins et al to examine airport operations, as well as its applicability to the study of other service industry processes.